PENGUATAN DAYA INGAT MAHASANTRI MELALUI MNEMONIC LEARNING - Hasan Baharun (Nurul Jadid University, 2018)
This research presents the strengthening of mahasantri's memory towards Nahwu and Shorrof learning using mnemonic learning approach in Marhalah Tamhidiyah, Ma'had Aly Nurul Jadid Paiton Probolinggo. Mnemonic learning is an innovative and creative learning concept, which prioritizes fun learning and joy full learning, where students are invited to memorize while playing by utilizing all available media and learning resources around them. This research uses a qualitative method with a case study approach. The results of this research shows that the learning of Nahwu and Shorrof with the mnemonic learning approach in Marhalah Tamhidiyah Ma'had Aly Nurul Jadid Paiton Probolinggo is done through; first, making of learning materials or teaching materials that are interesting and innovative are intended to arouse the motivation of students, help and facilitate students in learning Nahwu and Sharraf easily, effectively and efficiently. Second, the use of song rhythms to facilitate and remember learning material. Third, making acronyms. Fourth, image links through key words. Fifth, Concept Maps Technique